Acinetobacter species identification by using tRNA spacer fingerprinting. - Ehrenstein, B (1996)
Identification of Acinetobacter spp. to the DNA group level by phenotypic techniques is problematic, and there is a need for an alternative identification method for routine use. The present study validated the suitability of a rapid identification technique based on tRNA spacer (tDNA) fingerprinting in comparison with that of a commercially available assay involving carbon source utilization tests (Biolog MicroStation System) for identifying the 21 DNA-DNA hybridization groups belonging to the genus. For this purpose, 128 strains identified previously by DNA-DNA hybridization were analyzed by both techniques. tDNA fingerprinting was highly reproducible and classified all strains into 17 groups. Six DNA groups belonging to the A. calcoaceticus-A. baumannii complex were grouped into two distinct clusters, indicating the high degree of genetic similarity within this complex. Strains of the more recently described DNA groups BJ13 to BJ16 were ambiguously grouped and displayed three pattern types. The software used with the commercial carbon source utilization method grouped the 128 strains into 12 clusters, explaining the less discriminatory power of this system. We conclude that tDNA fingerprinting offers a quick and reliable method for the routine differentiation of most Acinetobacter spp. at the subgenus level.